Analisis Kesehatan Laporan Keuangan Pada PT BPR Syariah Buana Mitra Perwira Dengan Menggunakan Metode Camel Tahun 2016 – 2020 - Laila maghfiroh; Muhammad Iqbal Surya Pratikto (Jurnal Manajerial, 2022)
Background - Financial Health of the People's Credit Bank There is an assessment to reflect the role of economic policy, to determine the target and assess the financial health of a bank in a certain period, so that it can be used to analyze and as an evaluation to be able to know the performance of banking management. Purpose - In the Aspect of Camel Assessment have quantification of financial ratio calculations that are useful for assessing the level of financial health of the bank, the higher the capital of the bank that is expected to be the better the performance of its operations and the greater the scale of the operation, the bank is measured by total assets. Design / Methodology / Approach - This research researchers used quantitative research methods. To be able to achieve the objectives need to present an important indicator to determine the financial condition of PT BPR Syariah Buana Mitra Officers. Results and Discussion - The results of the study show that the health level at PT BPR Syariah Buana Mitra Officers in 2016-2020 can be declared very healthy. This means that at this time PT BPR Syariah Buana Perwira is able to guarantee customers for every deposit provided by the Customer and can pay all its obligations in the form of savings deposits, demand deposits, deposits when billed and can fulfill all credit applications that are approved. Conclusion - Car Ratio Analysis, PDN ratio, R0E RATIO, BOPO, NI and NPF ratio analysis at PT BPR Syariah Buana Mitra Officers in 2016- 2020 categorized are very healthy. While the analysis of Rentability using RAA ratio at PT BPR Syariah Buana Mitra Officers in 2016-2020 is categorized as healthy. While the FDR ratio analysis is categorized enough healthy. Research implications - this study can be used as a basis for the financial level of financial levels for the people's credit banks which are currently popping up. With this analysis, it will make BPR managers to be able to predict how the health level of BPR finance is adjusted to the conditions at this time.